2022
DOI: 10.1111/aswp.12262
|View full text |Cite
|
Sign up to set email alerts
|

“Neither it had social work components nor experiential”: Students' perspectives of online fieldwork practice during COVID‐19 in India

Abstract: This paper explores social work students' perspectives of online fieldwork practice that emerged due to sudden disruption in field placement as a result of the outbreak of COVID‐19 in India. We have recruited and interviewed 32 Master's students from five north‐Indian universities to participate in the research. The study's findings highlight ill‐equipped agencies lacking social work components in online/virtual field placement. Also, ethical dilemmas in working virtually, disconnectedness from the field, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Educational institutions were advised to update their strategic plans, cancel all mass meetings, and implement a variety of safety measures for students and staff. Following the public health guidelines and protocols to contain COVID-19 (Negi & Azeez, 2022) as well as keeping in mind the objective to complete the academic year, distance education was identified as a way forward (Niemczyk et al, 2021;Petrova, 2021). Brazil adopted various measures to slow down the spread of the virus; however, the country was recovering from the 2015/2016 recession, therefore, their response to the pandemic was limited due to the frail state of the economy even prior to the pandemic.…”
Section: Impact Of the Pandemic On Brics Higher Education Institutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Educational institutions were advised to update their strategic plans, cancel all mass meetings, and implement a variety of safety measures for students and staff. Following the public health guidelines and protocols to contain COVID-19 (Negi & Azeez, 2022) as well as keeping in mind the objective to complete the academic year, distance education was identified as a way forward (Niemczyk et al, 2021;Petrova, 2021). Brazil adopted various measures to slow down the spread of the virus; however, the country was recovering from the 2015/2016 recession, therefore, their response to the pandemic was limited due to the frail state of the economy even prior to the pandemic.…”
Section: Impact Of the Pandemic On Brics Higher Education Institutionsmentioning
confidence: 99%
“…Moving to the next BRICS member state, the People's Republic of China was the first country to close schools selectively in February 2020 (Niemczyk et al, 2021). As in other contexts, the pandemic has disrupted the traditional face-to-face learning and research methods at Chinese universities (Li & Che, 2022;Negi & Azeez, 2022). The sudden shift to remote teaching and research practices influenced the academic performance and the physical and psychological well-being of Chinese students and staff (Li & Che, 2022).…”
Section: Impact Of the Pandemic On Brics Higher Education Institutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For field practicum in social work, the agency is expected to supervise and evaluate day‐to‐day tasks of the intern students assigned by the supervisors (Apgar & Parada, 2018). Davis and Mirick (2021) discovered that during the early period of COVID‐19, field education in social work went through sporadic disruptions like the absence of appropriate placement and lack of supervision and hands‐on practice (Kourgiantakis & Lee, 2020; Mishra et al, 2022; Negi & Azeez, 2022). Buchanan and Bailey‐Belafonte (2021) identified many other challenges amidst the spread of coronavirus, such as lack of online field practicum sites, supervisors having no experience in online monitoring, students doing phone calls instead of a home visit, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Buchanan and Bailey‐Belafonte (2021) identified many other challenges amidst the spread of coronavirus, such as lack of online field practicum sites, supervisors having no experience in online monitoring, students doing phone calls instead of a home visit, etc. In some cases, though remote learning practice was introduced (Davis & Mirick, 2021), students faced ethical dilemmas because of being involved in virtual practices (Negi & Azeez, 2022; Sarbu & Unwin, 2021). de Jonge et al (2020) revealed that COVID‐19 impacted Dutch social work in many ways that destructed the educational landscape of social work students.…”
Section: Introductionmentioning
confidence: 99%